Landasan Filosofis Pendidikan - Dhena Delviana Aulia; Roihatul Parida Maulidi; Marjohan Marjohan; Sholeh Hidayat; Ratna Sari Dewi (Departement of Mathematics Education, 2022)
Philosophy is a science that discusses the problems of human life and thought, in the world of philosophy education it must be used as an exercise in critical thinking. Education is a place where teachers and students work for the same goal, namely to make someone intellectually and emotionally capable. Therefore, it must be formed formally or informally. Given that education is normative and perspective, the philosophical basis of education is a very important field to study. We will also understand who we teach, what we teach and how we teach it thanks to our educational philosophy. It is a set of values that guides how we behave professionally in our work and how we respond to adversity. This article was created by conducting a descriptive study of sources that discuss the philosophical foundations of education. The focus of this article is an explanation of the basics of educational philosophy, namely the meaning of philosophy, the importance of educational philosophy, the field of educational philosophy, the main provisions of educational philosophy and its benefits. of educational philosophy. It is hoped that this research will be useful for the UNTIRTA Serang academic community, especially for postgraduate students in basic education who teach courses on the philosophical basis of education.